Digital Media and Documentary Antipodean Approaches (Springer International Publishing, 2018)
This collection of essays by Australian based practitioner-theorists brings together new research on interactive documentary making. The chapters explore how documentary theory and practice is influenced by digitisation, mobile phones, and new internet platforms. The contributors highlight the questions raised for documentary makers and scholars as new production methods, narrative forms, and participation practices emerge. The book presents an introduction to documentary techniques shaped by new digital technologies, and will appeal to documentary scholars, students, and film-makers alike.